Pola Penerapan Workshop Edusosiopreneurship Seni Lukis Memotret Kekayaan Alam Pacitan melalui Pendekatan Self Determination Theory dan Game-Based Learning untuk Hilirisasi Merchandise Komunitas - Iriaji, Iriaji; Ratnawati, Ike; Prasetyo, Abdul Rahman; Nazwa, Venina Nabilla; Hamdani, Ardiansyah Yusuf (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
This research aims to explore the pattern of applying painting edusosiopreneurship workshops as a means to photograph Pacitan's natural wealth and turn it into creative products in the form of community merchandise. The approach used is Self Determination Theory (SDT) to build participants' intrinsic motivation and Game-Based Learning (GBL) to create an interactive and fun learning experience. This workshop activity is designed to explore the visual potential of the local landscape of Pacitan and integrate it into the creative process of painting that is oriented towards social entrepreneurship. Through descriptive qualitative methods, data is collected through participatory observation, in-depth interviews, and process documentation. The results show that the application of SDT is able to increase the autonomy, competence, and connectedness of participants in the art creation process, while GBL plays an important role in maintaining participant involvement and accelerating knowledge transfer. The products produced from this workshop, in the form of merchandise such as tote bags, stickers, and postcards, not only display Pacitan's natural wealth, but also have selling value and educational value. Thus, this program can be a sustainable model of community-based arts downstreaming.